Upgrading performance of Ad Hoc On-demand Distance Vector (AODV) routing protocol in mobile ad hoc networks - Ahmad, Noor Azlan; K. Subramaniam, Shamala (2007)
There many operations in Ad Hoc On-demand Distance Vector Routing Protocol (AODV) involving the wireless mobile ad hoc networks. One of them is a route table entry that was maintained and updated the active route information. AODV only stores the ‘freshness’ route to destination by using the sequence number to store in its table entry. However, a problem arises regarding an insufficient of data packets received by destination to those sent by the source and a routing delay in AODV is still one of the issues in this area. This paper focuses on enhancing the performance of AODV routing protocol using a lifetime as its metrics. This metric will be combined with the sequence number that causes the AODV to improve the network performance. Simulation results are provided to demonstrate the improvement in packet delivery ratio and reduction of delay in AODV routing protocol. The OMNET++ is used to simulate the performance of the metrics.